Structure and features of spatial distribution of pine forests in the Pinega State Nature Reserve - Popov, Sergey Yu (Nature Conservation Research: Заповедная наука, 2017)
The Pinega State Nature Reserve (Russia) is located in the Arkhangelsk region in the northern taiga subzone. Pine forests cover less than 10% of the reserve area. The vegetation of this forest is classified based on 83 phytosociological relevés. It reveals 7 associations, which represent 3 groups of associations. Detailed characteristics of these syntaxa (including analysis of their biodiversity) is provided. The revealed syntaxa well differs in species composition. Under the environmental conditions (moisture, nutrition, nitrogen availability and acidity), they are divided into two large groups. Associations as Pinetum sphagnosum and Pinetum empetroso-myrtillosum have the smallest number of species, whereas Pinetum polytrichosum and Pinetum myrtilloso-hylocomiosum are the richest in species number. Habitats occupied by associations of pine forests in the Reserve form an incomplete ecological series in relation to both trophicity and humidity. Pine forests associations were much more spread in the past and evenly throughout the Reserve. They are now confined mainly to landscapes with karst landforms.